Female Involvement, Membership, and Centrality: A Social Network Analysis of the Hartlib Circle. Issue 4 (7th April 2017) - Bourke, Evan
Abstract: This article builds upon the pioneering work of Carol Pal, Lynette Hunter, Ruth Connolly and Michelle DiMeo by carrying out an extensive social network analysis of the Hartlib Papers. By adapting the methodology recently developed by Ruth Ahnert and Sebastian E. Ahnert to analyse Protestant letter networks memorialised in Foxe's Acts and Monuments, this article uses digital and visual tools to assess the importance of female involvement in the Hartlib Circle. It examines how integral female members were to the information flow of this network and the degree to which their positions in the network granted them influence over other members. Through this computational approach, this article also challenges the view that at its core the Hartlib Circle was made up of a group of male friends, arguing that Dorothy Moore Dury and Katherine Jones, Viscountess Ranelagh need to be recognised as integral elements of this network's core.